Epigenetic Epidemiology - Michels, Karin B. (Cham : Springer International Publishing : Imprint: Springer, 2022)
Now in its second edition, this book provides a state of the art overview on basic concepts of epigenetic epidemiology and a comprehensive review of the rapidly evolving field of human epigenetics. Epigenetics plays an important role in shaping who we are and contributes to our prospects of health and disease. Unlike our genetic inheritance, our epigenome is malleable throughout the lifecourse and is shaped by our environmental experiences. Population-based epidemiologic studies increasingly incorporate epigenetic components. These so called epigenome-wide association studies (EWAS) contribute substantially to our understanding of the relevance of epigenetic marks, such as DNA methylation, histone modification, and non-coding RNAs for disease causation. Written by leading experts in the field, the book opens with a comprehensive introduction of the principles of epigenetic epidemiology and discusses challenges in study design, analysis, and interpretation. It summarizes the latest advances in epigenetic laboratory techniques, the influence of age and environmental factors on shaping the epigenome, the epigenetic clock, and the role of epigenetics in the developmental origins hypothesis. The final part focuses on epigenetic epidemiology of various health conditions such as imprinting disorders, cancer, infectious diseases, inflammation and rheumatoid arthritis, asthma, metabolic disorder and vascular disease, as well as neurodevelopmental and psychiatric disorders. Given its scope, Epigenetic Epidemiology is an indispensable resource for researchers working in the field of human epigenetics.
Part 1: Basic Concepts and Methodologic Considerations -- The Human Epigenome -- Considerations in the Design, Conduct, and Interpretation of Studies in Epigenetic Epidemiology -- Laboratory Methods in Epigenetic Epidemiology -- Biostatistical Methods in Epigenetic Epidemiology -- Epigenome Reprogramming During Development -- The Role of Epigenetics in the Developmental Origins of Health and Disease -- Epigenetics and Assisted Reproductive Technology -- Imprinting Disorders -- The Utility of Twins for Epigenetic Analysis -- Age-Related Variation in DNA Methylation -- The Epigenetic Clock -- Influence of Environmental Factors on the Epigenome -- Part 2: Epigenetic Epidemiology of Complex Diseases -- Epigenetic Epidemiology of Cancer -- Epigenetic Epidemiology of Infectious Diseases -- Epigenetic Epidemiology of Inflammation and Rheumatoid Arthritis -- Asthma Epigenetics: Emergence of a New Paradigm? -- Epigenetic Epidemiology of Autism and other Neurodevelopmental Disorders -- Epigenetic Epidemiology of Psychiatric Disorders -- Epigenetic Epidemiology of Obesity and Type 2 Diabetes -- Epigenetics and Vascular Disease (Atherosclerosis).
Keywords: Epigenetics; Epidemiology; Molecular biology; Epigenetics; Epidemiology; Molecular Biology